Data driven how performance analytics delivers extraordinary sales results - Dearborn, Jenny (John Wiley & Sons, 2015)
A ""how-to"" guide to boosting sales through predictive and prescriptive analytics Data Driven is a uniquely practical guide to increasing sales success, using the power of data analytics. Written by one of the world's leading authorities on the topic, this book shows you how to transform the corporate sales function by leveraging big data into better decision-making, more informed strategy, and increased effectiveness throughout the organization. Engaging and informative, this book tells the story of a newly hired sales chief under intense pressure to deliver higher performance from her tea.
Includes bibliographical references and index. - Online resource; title from title page (Safari, viewed May 13, 2015)
Keywords: Sales management; Selling; Qualitative research; Big data; Ventes; Gestion; Vente; Recherche qualitative; Données volumineuses; selling